THE DISINHERITED - Ong, Han (New York : Farrar, Straus, and Giroux, 2004)
The Disinherited is the story of forty-four-year-old Roger Caracera, who returns to the land of his birth after nearly three decades in the United States. Once back in Manila for the funeral of his estranged father, Jesus, the corrupt, charismatic head of the family sugar dynasty, Roger is forced to confront everything he put behind him." "When Jesus Caracera's will is read, Roger is stunned to discover that he has been left a small fortune. Unable to live with his inheritance, and now viewed by his countrymen as the representative American (a local tabloid even refers to him as a General Douglas MacArthur look-alike), Roger decides to give his money away. But whom among the millions of needy Filipinos is he to choose?" "Traversing high and low life, societies rank and respectable, and with a cast of characters that includes a slum-dwelling boy hustler, a middle-aged American pederast, a rising Filipino tennis player, a calculating society matron, and a Peace Corps worker turned trophy wife, The Disinherited is an exploration of the impulse to do good and the paradoxical harm brought on by largesse.
Keywords: Americans -- Fiction; Americans Philippines -- Fiction; Psychological fiction